Identification of Protein Abundance Changes in Hepatocellular Carcinoma Tissues Using PCT–SWATH. Issue 1 (19th November 2018) - Zhu, Yi; Zhu, Jiang; Lu, Cong; Zhang, Qiushi; Xie, Wei; Sun, Ping; Dong, Xiaochuan; Yue, Liang; Sun, Yaoting; Yi, Xiao; Zhu, Tiansheng; Ruan, Guan; et al.
Abstract : Purpose: To rapidly identify protein abundance changes in biopsy‐level fresh‐frozen hepatocellular carcinoma (HCC). Experimental design: The pressure‐cycling technology (PCT) is applied and sequential window acquisition of all theoretical mass spectra (SWATH‐MS) workflow is optimized to analyze 38 biopsy‐level tissue samples from 19 HCC patients. Each proteome is analyzed with 45 min LC gradient. MCM7 is validated using immunohistochemistry (IHC). Results: A total of 11 787 proteotypic peptides from 2579 SwissProt proteins are quantified with high confidence. The coefficient of variation (CV) of peptide yield using PCT is 32.9%, and the R 2 of peptide quantification is 0.9729. Five hundred forty‐one proteins showed significant abundance change between the tumor area and its adjacent benign area. From 24 upregulated pathways and 13 suppressed ones, enhanced biomolecule synthesis and suppressed small molecular metabolism in liver tumor tissues are observed. Protein changes based on α‐fetoprotein expression and hepatitis B virus infection are further analyzed. The data altogether highlight 16 promising tumor marker candidates. The upregulation of minichromosome maintenance complex component 7 (MCM7) is further observed in multiple HCC tumor tissues by IHC. Conclusions and clinical relevance: The practicality of rapid proteomic analysis of biopsy‐level fresh‐frozen HCC tissue samples with PCT–SWATH has been demonstrated and promising tumor marker candidates including MCM7 are identified.